Ileal Transcriptomic Analysis in Paediatric Crohn's Disease Reveals IL17- and NOD-signalling Expression Signatures in Treatment-naïve Patients and Identifies Epithelial Cells Driving Differentially Expressed Genes. (24th November 2020) - Ashton, James J; Boukas, Konstantinos; Davies, James; Stafford, Imogen S; Vallejo, Andres F; Haggarty, Rachel; Coelho, Tracy A F; Batra, Akshay; Afzal, Nadeem A; Vadgama, Bhumita; Williams, Anthony P; Beattie, R Mark; et al.
Abstract: Background and Aims: Crohn's disease [CD] arises through host-environment interaction. Abnormal gene expression results from disturbed pathway activation or response to bacteria. We aimed to determine activated pathways and driving cell types in paediatric CD. Methods: We employed contemporary targeted autoimmune RNA sequencing, in parallel to single-cell sequencing, to ileal tissue derived from paediatric CD and controls. Weighted gene co-expression network analysis [WGCNA] was performed and differentially expressed genes [DEGs] were determined. We integrated clinical data to determine co-expression modules associated with outcomes. Results: In all, 27 treatment-naive CD [TN-CD], 26 established CD patients and 17 controls were included. WGCNA revealed a 31-gene signature characterising TN-CD patients, but not established CD, nor controls. The CSF3R gene is a hub within this module and is key in neutrophil expansion and differentiation. Antimicrobial genes, including S100A12 and the calprotectin subunit S100A9, were significantly upregulated in TN CD compared with controls [ p = 2.61 x 10 -15 and p = 9.13 x 10 -14, respectively] and established CD [both p = 0.0055]. Gene-enrichment analysis confirmed upregulation of the IL17-, NOD- and Oncostatin-M-signalling pathways in TN-CD patients, identified in both WGCNA and DEG analyses. An upregulated gene signature was enriched for transcripts promoting Th17-cell differentiation and correlated with prolonged time to relapse [correlation-coefficient-0.36, p = 0.07]. Single-cell sequencing of TN-CD patients identified specialised epithelial cells driving differential expression of S100A9 . Cell groups, determined by single-cell gene expression, demonstrated enrichment of IL17-signalling in monocytes and epithelial cells. Conclusions: Ileal tissue from treatment-naïve paediatric patients is significantly upregulated for genes driving IL17-, NOD- and Oncostatin-M-signalling. This signal is driven by a distinct subset of epithelial cells expressing antimicrobial gene transcripts.